Mass Spectrometry-Based Proteomics of Endoscopically-Collected Pancreatic Fluid in Chronic Pancreatitis Research - Paulo, Joao A. (2011)
Mass spectrometry-based investigation of pancreatic fluid enables the high-throughput identification of proteins present in the pancreatic secretome. Pancreatic fluid is a complex admixture of digestive, inflammatory, and other proteins secreted by the pancreas into the duodenum, and thus is amenable to mass spectrometry-based proteomic analysis. Recent advances in endoscopic techniques, in particular the endoscopic pancreatic function test (ePFT), have improved the collection methodology of pancreatic fluid for proteomic analysis. Here, we provide an overview of mass spectrometry-based proteomic techniques as applied to the study of pancreatic fluid. We address sample collection, protein extraction, mass spectrometry sample preparation and analysis, and bioinformatic approaches and summarize current mass spectrometry-based investigations of pancreatic fluid. We then examine the limitations and the future potential of such technologies in the investigation of pancreatic disease. We conclude that pancreatic fluid represents a rich reservoir of potential biomarkers and that the study of the molecular mechanisms of chronic pancreatitis may benefit substantially from mass spectrometry-based proteomics.